Nylon 6 resin composition and method for producing the same

JP2025034560APending Publication Date: 2025-03-13TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023141020
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、衣料用繊維製造時に良好な製糸性が得られ、且つ高い白度と意匠性を演出することができるナイロン6樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034560000001
    Figure 2025034560000001
  • Figure 2025034560000002
    Figure 2025034560000002
Patent Text Reader

Abstract

To provide a nylon 6 resin composition which can obtain good spinning property when a fiber for clothing is produced, and can present high whiteness and designability.SOLUTION: A nylon 6 resin composition has a weight ratio (nylon 6 component / titanium oxide) of a nylon 6 component to titanium oxide of 40 / 60 to 95 / 5 wt.%, contains chemically recycled nylon 6, and has filtration pressure rising speed (5 μm filter in heating and melting at 280°C) of 3.0 Mpa / hour or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nylon 6 resin composition which contains a resin obtained by chemical recycling and contains titanium oxide at a high concentration, but which suppresses an increase in filtration pressure. [Background technology]

[0002] Polyamides have excellent mechanical, chemical and thermal properties and are therefore widely used in textile applications such as clothing and industrial applications, as well as in engineering plastics and films.

[0003] When polyamide is used for fiber applications or molded products, titanium dioxide is added to suppress transparency (matte finish) and improve whiteness. In particular, for clothing applications, it has been proposed to add titanium dioxide in high concentrations to achieve high designability, high functionality, and texture.

[0004] For example, Patent Documents 1 to 3 propose polyamide fiber products or resin products containing a high concentration of coated titanium oxide. Patent Document 1 proposes that titanium oxide particles are coated with an inorganic material to suppress thermal deterioration and improve light resistance. Patent Document 2 proposes mixing low-viscosity molten polyamide and titanium oxide particles in an extruder to maintain good dispersibility of the titanium oxide particles and mitigate the pressure rise of the filtration filter immediately before extrusion. Patent Document 3 proposes a specific adjustment method to maintain good dispersibility of titanium oxide particles and mitigate the pressure rise of the filtration filter. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2017-014397 A [Patent Document 2] JP 2002-129011 A [Patent Document 3] Patent Publication No. 2021-155525 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in Patent Documents 1 and 2, titanium oxide is melt-kneaded to contain a high concentration of titanium oxide, so that the titanium oxide is prone to aggregation and coarse particles are easily generated.

[0007] In the case of clothing fibers, the single fiber fineness is made finer to improve the feel and texture, and complex irregular cross sections including thin parts in the longitudinal direction of the yarn are made to impart functionality. If a large amount of agglomerated coarse particles of titanium oxide are contained in the production of clothing fibers, the agglomerated coarse particles will remain in the spinneret holes during melt spinning, causing discharge problems, leading to yarn breakage and defective formation of the irregular cross section. Furthermore, if agglomerated coarse particles are contained in the yarn, the stress under high tension during drawing and winding is less likely to be distributed throughout the yarn, causing yarn breakage and fuzzing.

[0008] One way to suppress the generation of these coarse aggregates is to add a dispersant suitable for titanium dioxide particles; however, when titanium dioxide is mixed in high concentrations, this can actually hasten the increase in filtration pressure due to an increase in the complex formed by the interaction between the titanium dioxide coating component (an anti-degradation agent for improving light resistance) and the dispersant.

[0009] The method described in Patent Document 3 focuses on the structure of the dispersant and proposes a technique for suppressing the complex and mitigating the increase in filtration pressure by a specific adjustment method. However, although it was possible to mitigate the increase in filtration pressure, the control method is special and very limited, and in addition, it is necessary to adjust the amount of dispersant when controlling it, making it difficult to expand the production volume, and so the problem of the increase in filtration pressure of nylon 6 resin compositions containing high concentrations of titanium oxide remains industrially.

[0010] The present invention has been made to solve the above problems, and it is an object of the present invention to provide a nylon 6 resin composition containing a high concentration of titanium dioxide, which can mitigate an increase in filtration pressure during the process and provide good spinnability during the production of clothing fibers, and a method for producing the same. [Means for solving the problem]

[0011] In order to solve the above problems, the present invention comprises the following configuration. (1) A nylon 6 resin composition having a weight ratio of nylon 6 components to titanium oxide (nylon 6 components / titanium oxide) of 40 / 60 to 95 / 5% by weight, which contains chemically recycled nylon 6 and has a filtration pressure increase rate (5 μm filter when heated and melted at 280°C) of 3.0 MPa / hour or less. (2) The nylon 6 resin composition according to (1) above, which contains 0.1 to 1.0% by weight of a dicarboxylic acid in the nylon 6 component. (3) A method for producing a nylon 6 resin composition according to (1) or (2) above, characterized in that titanium oxide is added to an aqueous ε-caprolactam solution having a pH of 4.5 to 6.5, which is mixed with ε-caprolactam obtained by depolymerizing a recycled nylon 6 product, and the mixture is subjected to liquid phase polymerization. Effect of the Invention

[0012] According to the present invention, it is possible to provide a nylon 6 resin composition which can provide good spinnability during the production of clothing fibers and can also provide high whiteness and design properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below. In the nylon 6 resin composition of the present invention, the weight ratio of the nylon 6 component to titanium oxide (nylon 6 component / titanium oxide) is 40 / 60-95 / 5% by weight. It is preferably 60 / 40-92 / 8% by weight, and more preferably 80 / 20-90 / 10% by weight. The higher the titanium oxide content, the higher the whiteness and designability of the resulting fiber, but the effect gradually saturates. On the other hand, during fiber production, the spinnability is reduced due to the coarse agglomerated particles of titanium oxide. When the titanium oxide content is 5-60%, excellent whiteness and excellent designability are exhibited. In addition, the texture can be further improved. When the titanium oxide content is less than 5%, the whiteness is insufficient and the designability is reduced. When the titanium oxide content exceeds 60%, the agglomerated particles of titanium oxide significantly deteriorate the spinnability, such as an increase in filtration pressure and thread breakage.

[0014] The nylon 6 resin composition of the present invention contains chemically recycled nylon 6. Chemically recycled nylon 6 means that it contains ε-caprolactam (hereinafter referred to as recycled lactam) produced by depolymerizing recycled nylon 6 products. Recycled lactam is made from recycled nylon 6 products, and therefore contains other resin components such as nylon 66, which is preferably used in fishing nets and clothing, and polyester. Therefore, these resin components are also depolymerized to contain small amounts of dicarboxylic acids. Examples of dicarboxylic acids include aliphatic dicarboxylic acids such as adipic acid, sebacic acid, and succinic acid, and aromatic dicarboxylic acids such as terephthalic acid and isophthalic acid.

[0015] In the nylon 6 resin composition of the present invention, the ratio of dicarboxylic acid is preferably 0.1 to 1.0% by weight relative to the nylon 6 resin composition. More preferably, it is 0.3 to 0.8% by weight. By making the ratio of dicarboxylic acid 0.1% by weight or more, the aggregation of titanium oxide is suppressed. As a result, there is no sudden increase in filtration pressure during fiber production, and spinnability is improved. In addition, since the incorporation of aggregated coarse particles of titanium oxide into the fiber is suppressed, not only is thread breakage reduced and spinnability further improved, but mechanical properties such as fluff suppression and strength maintenance can also be controlled. In addition, by making the ratio 1.0% by weight or less, high viscosity stability is obtained during melting, and good spinnability can be expressed.

[0016] The nylon 6 resin composition of the present invention has a filtration pressure rise rate ΔP of 3.0 MPa / hour or less when melted at 280°C using a 5 μm filter. It is preferably 2.0 MPa / hour or less. If it exceeds 3.0 MPa, the filtration pressure rise during liquid phase polymerization and melt spinning is significant, which increases the frequency of filter replacement work, increases the amount of work and increases costs, making it unrealistic for production. In addition, a high filtration pressure rise rate indicates that there are many coarse particles (foreign matter) of titanium oxide aggregates, and foreign matter that has slipped through the filter is undesirable because it leads to deterioration in spinnability due to thread breakage during drawing or winding, deterioration in quality due to frequent fluffing, and deterioration in mechanical properties such as strength.

[0017] In the method for producing recycled lactam according to the present invention, the recycled lactam is generally produced by depolymerizing the nylon 6 recycled product to recover ε-caprolactam and purifying the recycled lactam. The nylon 6 recycled product is pre-consumer waste and / or post-consumer waste. The types of waste are not limited. For example, the pre-consumer waste is the washed-out waste from the spinning process, thread breakage, and extrusion waste, and the post-consumer waste is recovered clothing products, fishing nets, ropes, etc. Any method may be used for depolymerization. For example, the nylon 6 recycled product is melted and depolymerized by heating. In this case, a catalyst may be used, and the process may be carried out in the absence (dry type) or presence (wet type) of water. The pressure during depolymerization may be reduced pressure, normal pressure, or increased pressure. The depolymerization temperature is 100°C to 400°C, preferably 200°C to 350°C, and more preferably 220°C to 300°C. If the temperature is low, the nylon 6 recycled product does not melt, and the depolymerization speed is slow. If the temperature is high, the nylon 6 monomer (i.e., ε-caprolactam) will decompose, resulting in a decrease in the purity of the recovered ε-caprolactam. Any method can be used to purify the recovered ε-caprolactam. For example, it can be a precision distillation method, a method of distilling under reduced pressure with the addition of a small amount of sodium hydroxide, a method of treating with activated carbon, a method of treating with ion exchange, a method of recrystallization, etc.

[0018] In the production of the nylon 6 resin composition of the present invention, the pH of the ε-caprolactam aqueous solution is 4.5 to 6.5. The pH of the ε-caprolactam aqueous solution using only virgin lactam is generally 7.0 to 8.5. In addition, the titanium oxide particles are surface-coated with an anti-deterioration agent to improve light resistance, and a dispersant is generally used to improve the dispersibility of titanium oxide when added during the polymerization of nylon 6. In particular, when titanium oxide is highly concentrated, this coating adversely affects the dispersibility when the pH of the ε-caprolactam aqueous solution shifts to the basic side. As a result, the dispersibility of titanium oxide is hindered, and an increase in filtration pressure occurs.

[0019] The present inventors have found that when recycled lactam is mixed into the ε-caprolactam to be fed, the pH of the ε-caprolactam aqueous solution shifts to the acidic side due to the dicarboxylic acid contained in the recycled lactam, improving the dispersibility of titanium oxide. If the pH is less than 4.5, the dicarboxylic acid is present in excess in the ε-caprolactam aqueous solution, reducing the polymerization reactivity and the quality of the resulting nylon 6 resin composition. In addition, titanium oxide is easily aggregated, and the filtration pressure rise rate ΔP of the resulting nylon 6 resin composition also increases. If the pH is more than 6.5, the dispersibility of titanium oxide is inhibited, causing an increase in filtration pressure, and the filtration pressure rise rate ΔP of the resulting nylon 6 resin composition also increases. Therefore, by mixing virgin lactam and recycled lactam and setting the pH of the ε-caprolactam aqueous solution to 4.5 to 6.5, the dispersibility and polymerization reactivity of titanium oxide become good, and the filtration pressure rise rate ΔP of the resulting nylon 6 resin composition can be controlled to 3 MPa / s or less. It is preferably 5.0 to 6.0.

[0020] In order to adjust the pH of the aqueous ε-caprolactam solution to 4.5 to 6.5, 20% by weight or more of recycled lactam is mixed with respect to the amount of ε-caprolactam. The mixing ratio of recycled lactam is preferably 20 to 80% by weight, more preferably 20 to 50% by weight, with respect to the amount of ε-caprolactam.

[0021] The method for producing the nylon 6 resin composition of the present invention is not particularly limited. For example, the composition can be produced by the steps of raw material preparation, mixing, concentration, liquid phase polymerization, discharge and cooling, cutting, extraction and dehydration. The nylon 6 resin composition of the present invention can be polymerized by a conventional method. For example, a mixture of ε-caprolactam (containing 20% ​​by weight or more of recycled lactam) containing a small amount of water and titanium oxide is pressurized to 0.98 MPa in a polymerization reactor, and the temperature is raised to 250°C while maintaining the pressure inside the reactor. After reaching 250°C, the pressure inside the reactor is released to atmospheric pressure over 60 minutes, and polymerization is carried out at atmospheric pressure for 90 minutes, after which the obtained polymer is discharged, cooled / cut, and pellets are obtained. Next, the pellets are retained for about 12 hours in a normal pressure vessel equipped with hot water in an amount 20 times the amount of the pellets, and unreacted monomers or oligomer components are extracted, followed by dehydration treatment.

[0022] Other additives can be added to the nylon 6 resin composition of the present invention depending on the application, as long as they do not impair the effects of the present invention. These additives can be added to the monomer raw material, added during the polymerization of the polyamide polymer, or added by melt mixing with the copolymer polyamide resin composition. Examples of these additives include antioxidants, heat stabilizers, weather resistance agents, release agents and lubricants, dyes, crystal nucleating agents, antistatic agents, flame retardants, other polymers, etc.

[0023] A method of adding titanium dioxide that can maintain good dispersibility is desirable because the decrease in dispersibility in the polymer and the generation of coarse particles due to aggregation increase the filtration pressure during fiber production and deteriorate the spinnability, quality, and mechanical properties such as thread breakage, fluff, and strength. Generally, titanium dioxide is added in the form of a powder or dispersed in a dispersion medium to the raw material preparation liquid before the liquid phase polymerization of the polymer, and a stabilized and homogenized state can be maintained throughout the polymerization reaction. Specifically, titanium dioxide is added to water to a concentration of about 20%, and the mixture is stirred, ground, and classified to form a good dispersion state, which is then added to the raw material preparation liquid of the polymer. EXAMPLES

[0024] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, the respective characteristic values ​​were calculated by the following methods.

[0025] <Relative viscosity of sulfuric acid (ηr)> Using polymer chips as samples, 0.25 g of the sample was dissolved in 100 ml of 98% sulfuric acid to make 1 g, and after shaking, the number of seconds for the sample solution to flow down at 25°C was measured using an Ostwald viscometer, and the time was calculated by dividing this by the time it took for 98% sulfuric acid alone to flow down, measured under the same conditions.

[0026] <Amino terminal group amount> The polymer chips were used as samples. 1.0 g of the sample was weighed out precisely, dissolved in 40 cc of a phenol-ethanol mixed solution (83.5:16.5, volume ratio), and then shaken. The sample was then neutralized by titrating with 0.02 N hydrochloric acid. The amount of 0.02 N hydrochloric acid required was divided by the amount of 0.02 N hydrochloric acid required for the phenol-ethanol mixed solution alone to calculate the concentration.

[0027] <Amount of dicarboxylic acid> The amount of dicarboxylic acid varies depending on the type of dicarboxylic acid. 1 H NMR and 13 It can be determined by C NMR. Specifically, the polymer chip is dissolved in deuterated HFIP, the spectrum is measured using a JEOL ECA-400, and the integral ratio is calculated from the peaks attributable to the nylon 6 and dicarboxylic acid components to calculate the amount of each component. For example, when the dicarboxylic acid is terephthalic acid, 1 It can be measured by 1 H NMR and calculated from the ratio of the 4H peak area derived from terephthalic acid at 8 to 8.5 ppm to the 2H peak area derived from nylon 6 at 3 to 3.5 ppm.

[0028] <Titanium oxide content> Polymer chips were used as samples, and were dried in advance at 150°C for 1.5 hours at normal pressure. 10.0 g of the sample was weighed out and completely incinerated using an electric heater or an electric furnace set at 700°C. The amount of the sample remaining after that was precisely weighed and divided by the weight before heating to calculate the mass.

[0029] <Filter pressure rise rate ΔP> The polymer chips were dried at 105°C for 8 hours under a vacuum of 133 Pa or less, and the filtration pressure increase rate was measured using a filterability tester (Melt Spinning Tester CII manufactured by Fuji Filter Industry Co., Ltd.). The filter was a Dynalloy Filter X5 manufactured by Watanabe Yoshikazu Seisakusho Co., Ltd. (mesh size 5 μm, filtration area 4.5 cm). 2 Filtration was performed using a filter with a polymer temperature of 280°C and a throughput of 4g / min. The difference in filtration pressure between 1 hour and 2 hours after the filter was attached was measured and used as the filtration pressure increase rate ΔP (MPa / hour). ·Judgment criteria ◎: ΔP≦1.0 ○: 1.0<ΔP≦2.0 △ :2.0<ΔP≦3.0 × :3.0<ΔP

[0030] <Whiteness = L value of tubular knit fabric> A cylindrical knitting machine (model number: TN-21) manufactured by Koike Machinery Co., Ltd. was used. Five 15 dtex raw yarns were combined to make a 75 dtex fiber sample, and a cylindrical knitted fabric (knit density: 50 yarns / 2.54 cm) was produced. The produced cylindrical knitted fabric was evaluated for the color tone L value of the cylindrical knitted surface using a color meter manufactured by Suga Test Instruments Co., Ltd., and classified according to the following criteria. ·Judgment criteria ◎: 60≦L value 〇: 45≦L value<60 △: 30≦L value<45 × : L value < 30

[0031] <Thread reeling property = number of thread breaks> The number of yarn breakages per ton was calculated, and the frequency of yarn breakage (times / ton) was classified according to the following criteria. ·Judgment criteria ◎: Number of thread breaks <3 ○: 3≦Number of thread breaks<6 △: 6≦Number of thread breaks<10 × :10≦Number of thread breaks

[0032] Example 1 A polymerization reactor was charged with 12.5% ​​water-containing ε-caprolactam (a mixture of 80% by weight of virgin lactam and 20% by weight of recycled lactam, pH 6.5), 0.2% by weight of dicarboxylic acid, and an aqueous dispersion slurry of titanium oxide with a concentration of 20% obtained by mixing titanium oxide TA-500 (manufactured by Fuji Titanium Co., Ltd.) and water.

[0033] After sealing the inside of the polymerization reactor with nitrogen, the pressure was increased to 0.98 MPa, and while maintaining the pressure inside the reactor, the temperature was increased to 250° C. After reaching 250° C., the pressure inside the reactor was released to atmospheric pressure over 60 minutes, and polymerization was carried out at atmospheric pressure for 90 minutes, after which the obtained polymer was discharged and cooled / cut into pellets.

[0034] Next, the pellets were transferred to a pressure vessel containing hot water in an amount 20 times the amount of the pellets, and allowed to stand for 12 hours at a water temperature of 98°C. Unreacted monomer or oligomer components were extracted, and then the pellets were dehydrated to obtain a final amino terminal group amount of 6.1 x 10 -5 A nylon 6 resin composition having a viscosity of 2.35 mol / g in sulfuric acid and a titanium oxide content of 10.0 wt % was obtained.

[0035] The resulting nylon 6 resin composition was dried to a moisture content of 0.135% by weight or less, and then melt-extruded at a rate of 37.777 g / min from a spinneret having 144 nozzle holes (hole diameter 0.16 mm, hole depth 0.32 mm) at a spinning temperature of 275° C. After melt-extrusion, the composition was cooled, oiled, entangled, and then taken up by a godet roller at 3280 m / min, and then stretched 1.3 times and heat-set at 155° C. to obtain nylon 6 fiber (6 yarns) with a total fineness of 15 decitex and 24 filaments at a take-up speed of 4200 m / min.

[0036] (Examples 2 to 4, Comparative Example 1) The production was carried out under the same conditions as in Example 1, except that the ratio of recycled lactam contained in the ε-caprolactam containing 12.5% ​​water was changed.

[0037] (Examples 5 to 8, Comparative Example 2, Comparative Example 3) The production conditions were the same as in Example 1, except that the amount of titanium oxide was changed.

[0038] The properties of the nylon 6 resin compositions obtained in Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Tables 1 and 2.

[0039] [Table 1]

[0040] [Table 2]

[0041] As shown in Tables 1 and 2, the nylon 6 resin compositions obtained in Examples 1 to 8 had a filter pressure rise rate ΔP of 3 MPa / hour or less, and good spinnability was obtained when producing clothing fibers. In addition, the whiteness of the obtained fibers was high, which can contribute to the presentation of design and the expression of functionality. This shows that products equipped with these good properties can be provided.

Claims

1. The nylon 6 resin composition has a weight ratio of nylon 6 component to titanium oxide (nylon 6 component / titanium oxide) of 40 / 60 to 95 / 5% by weight, contains chemically recycled nylon 6, and has a filtration pressure increase rate (5 μm filter when heated and melted at 280° C.) of 3.0 MPa / hour or less.

2. 2. The nylon 6 resin composition according to claim 1, wherein the nylon 6 component contains 0.1 to 1.0% by weight of a dicarboxylic acid.

3. 3. The method for producing a nylon 6 resin composition according to claim 1 or 2, characterized in that titanium oxide is added to an aqueous ε-caprolactam solution having a pH of 4.5 to 6.5, the aqueous ε-caprolactam solution being mixed with ε-caprolactam obtained by depolymerizing a recycled nylon 6 product, and then the aqueous ε-caprolactam solution is subjected to liquid phase polymerization.

Citation Information

Patent Citations

  • Titanium oxide-containing polyamide and method for producing the same

    JP2002129011A

  • Polyamide composition, molding, and reflection plate for LED

    JP2017014397A

  • Polyamide resin composition

    JP2021155525A